2018
DOI: 10.1049/iet-est.2017.0029
|View full text |Cite
|
Sign up to set email alerts
|

Hybridisation ratio for hybrid excitation synchronous motors in electric vehicles with enhanced performance

Abstract: For electric vehicles (EVs) with severe acceleration requirement, the selected motor would be inevitably overdesigned to meet the acceleration requirement. To address this, the motor constant power speed ratio (CPSR) should be increased to remove part of the overdesign. There are different flux weakening techniques that are used to increase motor maximum speed (and increase the CPSR). Among them, hybrid excitation synchronous motor (HESM) advantages have been benefited in this study. CPSR depends on hybridisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Several studies have expressed the ratio of the flux from the FW to the flux from the PM, for example, the study of the influence of the "ratio of hybridization" by Ammar et al [10,[29][30][31][32].…”
Section: The Excitation Fluxmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have expressed the ratio of the flux from the FW to the flux from the PM, for example, the study of the influence of the "ratio of hybridization" by Ammar et al [10,[29][30][31][32].…”
Section: The Excitation Fluxmentioning
confidence: 99%
“…Such benefits have been studied by Cinti et al [34], who compared PM machines and HE machines, and showed the advantages of operating with a good efficiency at variable speeds. Such strategies for flux weakening in hybrid excitation have been studied by Giulii-Capponi et al [39,40], Amara et al [29], ShahMohammadi et al [32], and Michieletto et al [41].…”
Section: Advantage Of Variable Flux In Hybrid Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Leisure activity vehicles are typically characterized as being light and compact, but with a high acceleration and speed capabilities. In this regard, sizing problem should ascertain the minimum required component dimensions to satisfy the requested power for all the constraints specified in Table 2 [30]. Based on the specifications, the FC needs to be sized in a way to supply the maximum power for a long distance, continuous, and high-speed driving.…”
Section: Original Research Papermentioning
confidence: 99%
“…Hence, neglecting the influence of the temperature, magnetic saturation, and hysteresis loss [22], several basic equations of the HECPSM, including voltage, flux linkage and electromagnetic torque, can be expressed as…”
Section: Hecpsm Mathematic Modelmentioning
confidence: 99%